A Bibliometric Analysis of Carbon Dots in Sensors Application - Putro, Permono Adi; Hardhienata, Hendradi; Isnaeni, Isnaeni; Ahmad, Faozan; Khaerudini, Deni Shidqi; Prasetyo, Andhika Prima; Maddu, Akhiruddin (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2022)
The exponential increase in carbonaceous-based research has prompted the scientific community to apply it to numerous value-added applications. This paper aimed to systematically analyze the comprehensive contributions clusters of publications per year, country, institution, authors, and keywords-wise by using a quantitative review technique called bibliometric analysis. The data was retrieved from the Scopus database to identify the overall scientific trend results with the keyword "carbon dots as a sensor" from 2010 to 2020. The VOSviewer, WordItOut, and Datawrapper are selected as tools for bibliometric analysis and data visualization. In this work, the total citations from the Scopus Core Set and the total citations in the most recent year have only been used for the assessment of highly cited papers. The results showed that after 2014, the number of publications increased significantly with the work related to “carbon dots as sensors.” Thus, comprehensive journals like the Angewandte Chemie - International Edition were the most popular in publishing articles, contributing to almost 6.39% of the research area. The country-wise analysis revealed that China accounted for more than 67.18% of the articles published, followed by the United States and India, comprising 6.24% and 6.13%, respectively. Lastly, keyword cluster analysis revealed five major research hotspots for future discussion. Thus, this analysis provides an important starting point for further studies on research concerning the direction of "carbon dots as a sensor" for positive development in the research area.